1996
DOI: 10.1136/gut.38.5.694
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal motor abnormalities in patients with functional dyspepsia demonstrated by ambulatory manometry.

Abstract: Aims/Methods-In 30 patients with functional dyspepsia and in 20 healthy volunteers, ambulatory duodenojejunal manometry was performed to examine the interdigestive and postprandial small intestinal motility patterns in relation to symptoms. Results-In the fasting state, the number of migrating motor complex cycles mean (SEM) was significantly lower in patients, especially in patients with dysmotility-like dyspepsia, than in control subjects (3.8 (0.4), 2.6 (0.5), and 5.3 (0.7) cycles, respectively; p<005), due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
(12 reference statements)
5
27
1
Order By: Relevance
“…During the interdigestive period there were three quantitative parameters that were significantly different between the patient group and the healthy controls: in dyspeptics the incidence of antral or jejunal phase 3s was reduced and the relative contribution of phase 2 to the MMC cycle was increased. These observations confirm previous findings,6 7 and the reference values obtained in the healthy volunteers are in accordance with other studies using ambulatory manometry 2425 Phase 3 has been interpreted as having a housekeeper function by causing rapid aboral and effective propagation of intraluminal contents 19.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During the interdigestive period there were three quantitative parameters that were significantly different between the patient group and the healthy controls: in dyspeptics the incidence of antral or jejunal phase 3s was reduced and the relative contribution of phase 2 to the MMC cycle was increased. These observations confirm previous findings,6 7 and the reference values obtained in the healthy volunteers are in accordance with other studies using ambulatory manometry 2425 Phase 3 has been interpreted as having a housekeeper function by causing rapid aboral and effective propagation of intraluminal contents 19.…”
Section: Discussionsupporting
confidence: 92%
“…4 Motor patterns suggestive of small intestinal dysmotility with or without associated gastric dysmotility have also been described in patients with dyspepsia, both with conventional stationary1 3 5 as well as with ambulatory antroduodenal6 and duodenojejunal manometry 73 5 7 aberrant propagation of phase 3 of the MMC,5 7 longer durations of phase 2,7 a higher prevalence of burst activity,1-3 6 7 and an abnormal motor response after a meal 7. Ambulatory manometric evaluation has been noted to be superior to stationary manometry for evaluating patients with functional dyspepsia6 because it offers the possibility of studying motor function—especially interdigestive motor function—for prolonged periods of time and also because it increases the chances of detecting a possible relation between symptoms and motor abnormalities 8-10.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A study of 34 children and 35 adults with FD found a majority with abnormal motility with a neuropathic pattern observed most commonly [110] . Several studies of antroduodenal motility also demonstrate abnormalities in adults with FD [111,112] , but symptoms, intestinal dysmotility, and gastric emptying delays are not clearly correlated [112] . The relationship between motility studies is made even less clear in that a study of 31 adults with FD showed abnormal EGG was not associated with concurrent abnormalities in antroduodenal manometry [113] , and available pediatric data supports this concept [114] .…”
Section: Antroduodenal Manometrymentioning
confidence: 99%
“…Others have shown that dyspeptic patients have abnormal motility 1. This study hoped to go one step further and link symptoms with specific patterns of dysmotility by using prolonged ambulatory motility studies.…”
mentioning
confidence: 97%